2016
DOI: 10.1097/pep.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Six-Minute Walk Test in Children With Spastic Cerebral Palsy and Children Developing Typically

Abstract: A range of 6-minute walk distance reference values for children with spastic CP and children with TD were established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
(40 reference statements)
3
38
1
1
Order By: Relevance
“…Thus, it appears that in this relatively well functioning group of children with CP, muscle fatigue occurs more prominently in lower leg muscles, but not upper leg muscles, than in typically developing peers during 5 minutes of walking at self‐paced speed. This lower leg muscle fatigue could be one of the contributing factors to reduced walking capacity reported in children with CP …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it appears that in this relatively well functioning group of children with CP, muscle fatigue occurs more prominently in lower leg muscles, but not upper leg muscles, than in typically developing peers during 5 minutes of walking at self‐paced speed. This lower leg muscle fatigue could be one of the contributing factors to reduced walking capacity reported in children with CP …”
Section: Discussionmentioning
confidence: 99%
“…This lower leg muscle fatigue could be one of the contributing factors to reduced walking capacity reported in children with CP. 21 The fact that muscle fatigue most prominently occurs in the lower leg muscles of children with CP during selfpaced walking versus other muscle groups can be explained by several factors. Previous research has shown that strength is mostly affected in the lower leg muscles, more specifically the calf muscles, of children with CP when comparing lower limb muscle strength levels in typically developing peers.…”
Section: Discussionmentioning
confidence: 99%
“…Participants performed the test barefoot without using an assistive device. The 6-Minute Walk Test (6MWT) assessed children's walking aerobic capacity (Maher et al, 2008;Fitzgerald et al, 2016). Each subject was asked to ambulate around a fixed course as safely and quickly as possible.…”
Section: Functional Mobilitymentioning
confidence: 99%
“…Standard phrases of encouragement are provided at the end of each minute and there is no warm-up. The 6MWT has been widely used as a test of submaximal exercise test among individuals living with many different conditions, including: Alzheimer disease (Ries, Echternach, Nof, & Gagnon Blodgett, eujapa.upol.cz 2009), osteoarthritis (Bingchen et al, 2008), severe heart and lung disorders (Brown & Wise, 2007), Parkinson's disease (Falvo & Earhart, 2009), cerebral palsy (Fitzgerald, Hickey, Delahunt, Walsh, & O'Brien, 2016), and cystic fibrosis (Gruet, Brisswalter, Mely, & Vallier, 2010).…”
Section: Introductionmentioning
confidence: 99%